Persepsi Akuntan Tentang Penerapan Prinsip-Prinsip Akuntansi Syariah Dalam Lembaga Keuangan Syariah - Nur Anisah; Langgeng Prayitno Utomo (Assets: Jurnal Akuntansi dan Pendidikan, 2017)
This study aims to determine the perception of accountants on accounting principles of sharia in Islamic financial institutions. This type of research using qualitative methods to survey respondents is an accountant who worked at BMT As-Salam and BMT-Mojoagung Maslahah in Jombang. The results showed that according to the accountant at the two institutions that they work BMT place already apply accounting principles of sharia, the humanist, emancipatory, transcendental and teological although its application is not perfect. Balance and fairness to the owners, managers and users of funds may be a dilemma in operation.Keywords: perception, accountants, accounting principles of sharia, Islamic financial institutions